Petrologia das Rochas Vulcânicas da Península Fildes, Ilha Rei George, Antártica - MACHADO, ADRIANE; CHEMALE JUNIOR, FARID; DE LIMA, EVANDRO FERNANDES; FIGUEIREDO, ANA MARIA GRACIANO (Pesquisas em Geociências, 1998)
The Paleocene-Eocene volcanic activity in the Fildes Peninsula is marked by basaltic to basalt-andesitic lavas and dykes with subordinate amounts of dacites and rhyolites. Studies of mineral chemistry point to calcic plagioclase (An72-95) and augitic pyroxene phenocrysts and seldom grains of pigeonite and bronzite. Rock chemistry of ten samples indicates a calk-alkaline affinity based on enrichment in LILE and LREE, moderate contens of Zr, negative anomalies of Nb and Ti in multicationic diagrams, the high Al2O3 contents and also because CaO≥FeOT. High contents of FeOT and limited enrichment of SiO2 are caused by fractionation of mafic silicates which probably occurred without cogenetic Ti-magnetite crystallization. The low content of Ni, Cr, Co and MgO in the basic rocks also support this hypothesis. 87Sr/Sr86 initial rations from 0.7033 to 0.7037 and ƐNd positive values (t=55 Ma) of 6.52 and 6.72 suggest a mantle source with few or without assimilation of continental crust. This magmatic activity is thus related to the Mesozoic and Cenozoic subduction in the Antartic region which gave rise to the island arc of the South Shetland Islands.